Thwarted interpersonal needs and suicide ideation: Comparing psychiatric inpatients with bipolar and non-bipolar mood disorders. (30th December 2016) - Taylor, Nathanael J.; Mitchell, Sean M.; Roush, Jared F.; Brown, Sarah L.; Jahn, Danielle R.; Cukrowicz, Kelly C.
Abstract: Psychiatric inpatients are at heightened risk for suicide, and evidence suggests that psychiatric inpatients with bipolar mood disorders may be at greater risk for suicide ideation compared to those with non-bipolar mood disorders. There is a paucity of research directly comparing risk factors for suicide ideation in bipolar versus non-bipolar mood disorders in an inpatient sample. The current study sought to clarify the association between two constructs from the interpersonal theory of suicide (i.e., perceived burdensomeness and thwarted belongingness) in leading to suicide ideation among psychiatric inpatients with bipolar and non-bipolar mood disorders. Participants were ( N =90) psychiatric inpatients with a bipolar ( n = 20) or non-bipolar mood disorder ( n =70; per their medical charts). Perceived burdensomeness, but not thwarted belongingness, was significantly associated with suicide ideation after adjusting for other covariates. This suggests perceived burdensomeness may play a key role in suicide ideation among psychiatric inpatients with any mood disorder and highlights the importance of assessment and intervention of perceived burdensomeness in this population. Contrary to our hypothesis, mood disorder group (i.e., bipolar versus non-bipolar) did not moderate the relations between perceived burdensomeness/thwarted belongingness and suicide ideation. Highlights: Perceived Burdensomeness was significantly associated with suicide ideation. Thwarted Belongingness was not significantly associated with suicide ideation. The strength of these associations did not differ by mood disorder type. Individuals with bipolar disorder have greater perceived burdensomeness. Thwarted belongingness and suicide ideation did not differ by mood disorder type.